High resolution silicon array detector implementation in an inline MRI‐linac. Issue 4 (28th January 2020) - Alnaghy, Sarah J.; Causer, Trent; Roberts, Natalia; Oborn, Brad; Jelen, Urszula; Dong, Bin; Gargett, Maegan; Begg, Jarrad; Liney, Gary; Petasecca, Marco; Rosenfeld, Anatoly B.; Holloway, Lois; et al.
Abstract : Purpose: Dynamic dosimaging is a concept whereby a detector in motion is tracked with magnetic resonance imaging (MRI) to validate the amount and position of dose in a radiation therapy treatment on an MRI‐linac. This work takes steps toward the realization of dynamic dosimaging with the novel high resolution silicon array detector: MagicPlate‐512 (M512). The performance of the M512 was assessed in a 1.0 T inline MRI‐linac, without simultaneous imaging and then during an imaging sequence, both during dosimetry. MR images were acquired to determine the effect of the detector and its components on image quality. Methods: Beam profiles were measured using the M512 on the Australian MRI‐Linac and a comparison made with Gafchromic EBT3 film to investigate any intrinsic magnetic field effects in the silicon. The M512 has 512 sensitive volumes, each 0.5 × 0.5 × 0.037 mm 3 in dimension, organized in a two‐dimensional array. Small field sizes up to 4.2 × 3.8 cm 2 were investigated in both solid water and then solid lung phantoms. Beam profiles taken at 1.0 T were compared to 0 T conditions, and also to profiles taken during a gradient echo (GRE) imaging sequence. Differences in 80%‐20% penumbral width and full width at half maximum (FWHM) were investigated. Localizer MR images were acquired of the detector adjacent to a water phantom. Results: Good agreement was observed between the M512 and film, with average differences in penumbral width and FWHM of <1 mm in the absence of the imaging sequence. Concurrent imaging widened the penumbra by up to 1.2 mm due to RF noise affecting the detector; film profiles were unchanged. Magnetic resonance images were affected by noise, in particular, due to the large amount of aluminum present, as well as from the USB cable, which acted as an antenna. Unfortunately, due to these issues, suitable dynamic dose imaging was not achieved with the current M512/phantom configuration and the MRI‐linac. However, progress was made toward achieving this goal for future work. Conclusions: The M512 silicon array detector successfully measured high‐resolution beam profiles in agreement with Gafchromic film to within an average of <1 mm on the first MRI‐linac in Australia. More effective noise reduction will be required for the achievement of dynamic dosimaging in the future.